Enhancing sustainability within portugal's ornamental stone industry's industry 4.0 ecosystem supply chain - Duarte de Almeida, I.; Silva, A. (Proceedings of 27th Cambridge International Manufacturing Symposium, 2023)
Industry 4.0 (I4.0) has brought digital disruptions to supply chains (SC), which interest researchers and practitioners. This paper presents a theoretical and conceptual approach that explores how technological advances are changing SC processes in the Portuguese ornamental stone industry (POS). It uncovers innovative capabilities within the SCOR model that improve sustainable performance, social responsibility, and achievement of the 17 Sustainable Development Goals. Systematic literature review links I4.0 capabilities to SCOR processes and assesses the impact on SDGs. I4.0 supports POS-SC sustainability, but the SDGs' success depends on stakeholder engagement/collaboration and training. This paper informs the interplay between I4.0 and sustainability at POS-SC, calling for collaborative efforts.